Phenotypic Variation Through Ontogeny: Thyroid Axis Disruption During Larval Development in the Frog Pleurodema borellii - Fabrezi, Marissa; Cruz, Julio César (Frontiers in Ecology and Evolution, 2021)
Studies of the effects of thyroid hormones on larval development in the frog Xenopus spp. have provided baseline information to identify developmental constraints and elucidate genetic and hormonal mechanisms driving development, growth, and life history transitions. However, this knowledge requires data based on other anurans to complete a comprehensive approach to the understanding of larval developmental diversity and phenotypic variation through ontogeny. Mesocosm experiments provide realistic data about environmental conditions and timing; this information is useful to describe anuran larval development and/or analyze endocrine disruption. In this study, mesocosm experiments of the larval development of the frog Pleurodema borellii were conducted to explore the consequences of thyroid axis disruption; the sensitivity of tadpoles to the methimazole (2.66 mg/l) and thyroxine (T4) (1.66 µg/l) was compared. These concentrations were selected based on previous studies in Pleurodema borellii. We test the effects of methimazole and thyroxine on development in early exposure (from the beginning of larval development) and late exposure, 18 days after hatching, with doses administered every 48 hours. Tadpoles were evaluated 31 days after hatching. Methimazole caused moderate hypertrophy of the thyroid gland, alteration in the growth rates, differentiation without inhibition of development, and an increase of developmental variability. Thyroxine produced slight atrophy of the thyroid gland, accelerated growth rates and differentiation, and minor developmental variability. In tadpoles at stages previous to metamorphose, skull development (differentiation of olfactory capsules, appearance of dermal bones, and cartilage remodeling) seemed to be unaltered by the disruptors. Moreover, similar abnormal morphogenesis converged in specimens under methimazole and thyroxine exposures. Abnormalities occurred in pelvic and pectoral girdles, and vent tube, and could have been originated at the time of differentiation of musculoskeletal tissues of girdles. Our results indicate that premetamorphic stages (Gosner Stages 25–35) are sensitive to minimal thyroid axis disruption, which produces changes in developmental rates; these stages would also be critical for appendicular musculoskeletal morphogenesis to achieve the optimal condition to start metamorphosis.